The Role of Gender Diversity in Moderating the Effect of Profitability, Firm Size, and Solvency on the Stock Price of Islamic Banks Listed on IDX - Budhi Pamungkas Gautama; Davu Raissa Elazar; Eka Surachman; Yoga Perdana; Asep Miftahuddin; Iqbal Luthfi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study examines the relationship between gender diversity and the stock prices of Islamic banks in Indonesia, as well as the effects of profitability, business size, and solvency. The study is motivated by the importance of fundamental performance in establishing the market value of Islamic banks, which is especially relevant given the growing emphasis on inclusive governance. Using panel data regression and Moderated Regression Analysis (MRA), this study employs a quantitative technique to analyze four Islamic banks listed on the Indonesia Stock Exchange from 2020 to 2024. The findings show that all three variables have a significant effect on stock prices. Finding that gender diversity moderates these associations albeit negatively suggests that a greater proportion of female directors tends to mitigate the effect of fundamental variables on stock prices. These results suggest that in order to achieve the goal of increasing the capital market value of Islamic banks, it is essential to strategically manage the leadership roles of women.